2022
DOI: 10.3389/fmars.2022.824973
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Dietary Crude Protein in Commercial Feeds for Shrimp and Halophytes in Marine Aquaponic Biofloc Systems

Abstract: Formulated diets for animals is the primary source of nutrients in aquaponic systems that need to maintain beneficial bacteria as well as for plants. Dietary protein is one of the expensive macronutrients in fish diets, especially when fishmeal is used, and it is the source of nitrogen (N) for other biotic components. Biofloc has the potential to serve as the supplement diet for shrimp and reduce the need of expensive protein. However, it is not clear if low dietary protein will be adequate to support the thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 61 publications
1
7
0
Order By: Relevance
“…After the first harvest (day 28), the concentration of TAN and NO2increased in all treatments in the present study (Figure 5 C and D), which is similar to results from other studies [21,83]. Chu and Brown [9] reported that the concentration of nitrogenous compounds increased after harvests, but the concentration of TAN did not increase to a hazardous level at the late stage, and the concentration of NO2remained within safe ranges throughout the experiment.…”
Section: Water Qualitysupporting
confidence: 91%
See 2 more Smart Citations
“…After the first harvest (day 28), the concentration of TAN and NO2increased in all treatments in the present study (Figure 5 C and D), which is similar to results from other studies [21,83]. Chu and Brown [9] reported that the concentration of nitrogenous compounds increased after harvests, but the concentration of TAN did not increase to a hazardous level at the late stage, and the concentration of NO2remained within safe ranges throughout the experiment.…”
Section: Water Qualitysupporting
confidence: 91%
“…In the present study, the potential reasons for TAN and NO2increasing beyond the safe range after harvest might be the frequency of inoculating probiotics, the C/N ratio, animal to plant ratio, the water source, or the ionic composition in the water. Chu and Brown [9,21,31] inoculated probiotics on a regular basis and maintained the C/N ratio at 12 and 15, which provided a better environment for heterotrophic bacteria to assimilate nitrogenous compounds. The lower C/N ratio and discontinuous inoculation in the present study could be one of the causes of the high concentration of TAN and NO2 -.…”
Section: Water Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…The high demand for energy for catabolism rather than protein deposition will result in a poor growth rate of fish when diets are excessively high in protein [ 28 ]. The decrease in growth as a result of high protein may be caused by the build-up of toxic nitrogen compounds, which can affect the growth of rockfish [ 29 , 30 ]. Therefore, the protein requirement of rockfish larvae fed granulated microdiets was estimated to be 54.0% according to the broken line analysis of weight gain of larval fish.…”
Section: Discussionmentioning
confidence: 99%
“…In commercial aquaponic setups, fish may undergo feed restrictions to maintain a balance between the aquaculture and hydroponic components (Chu & Brown, 2022). These strategies, aimed at controlling growth, preventing disease, preserving water quality, and enhancing energy efficiency, can include periodic fasting (Robaina et al, 2019).…”
Section: Introductionmentioning
confidence: 99%